An analysis of the Singapore bond market. - Choo, Hsun Yang (2014)
The Singapore Bond Market is still at its adolescent stage of development, and there has not been much coverage on this subject in the local research. It is surprising that the local research has neglected the significance of this market, which is able to provide additional opportunities for diversification and investment. In this research on the local bond market, the team will look at each and every aspects of the local bond market, providing useful information to investors and determining the attractiveness of the bond market via empirical studies.